MENGGUGAT EKSISTENSI PENJUALAN BARANG MELALUI INFOMERCIAL (Perlindungan Hukum Bagi Konsumen) - Eman Sulaiman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
This paper discusses the lawsuit against the sale of goods through infomercials with a review of the protection of rights for consumers. Infomercials with types of transactions in the eyes of consumers send money worth the price of goods plus shipping costs to sellers that have been advertised in the media. In this case, the buyer is in a helpless position. The type and quality of goods received by consumers is often not in accordance with advertising in the media. Therefore, the media not only profit from the infomercials, but also must be responsible for the truth of the advertisements.